The role of cardiac myocyte dimensions in the transition from hypertensive hypertrophy to cardiac dilatation - Correia, Raul Jose (My University, 2012)
The progression from compensated cardiac hypertrophy to decompensation and cardiac failure is accompanied by cardiac dilatation. As cardiac failure has a poor prognosis, it is imperative to prevent the progression to cardiac dilatation and heart failure. In this regard, an understanding of the mechanisms of cardiac dilatation is vital to guide optimal therapy to prevent heart failure. Although a number of factors have been shown to contribute to the development of cardiac dilatation, to date the role of alterations in cardiac myocyte dimensions remains unclear. Hence, the aim of the current study was to determine whether changes in cardiac myocyte dimensions contribute to the process of cardiac dilatation. Methods: Two models of cardiac dilatation in pressure-overload induced cardiac hypertrophy were assessed. One model was a natural progression model, in which 18 spontaneously hypertensive rats (SHR), were assessed at 23 months of age (an age when left ventricular hypertrophy is noted to have progressed to left ventricular decompensation, dilatation and heart failure in approximately 50% of rats). The second model, a pharmacological model, was induced in 14 month old SHR (n=9) by chronic beta-adrenoreceptor activation [0.02mg/kg isoproterenol (ISO) twice daily for 4.5 months]. Chronic beta-adrenoreceptor activation in SHR, enhances the progression from compensated left ventricular hypertrophy to left ventricular dilatation. Nine normotensive Wistar Kyoto (WKY) rats were the controls for both models. Left ventricular dilatation was defined as an increase in left ventricular radius determined at controlled filling pressures using piezo-electric transducers. The classification of rats as being in heart failure was based upon the presence of pleuropericardial effusions and / or atrial thrombi. Cardiac myocytes were isolated and dimensions determined using both light microscopy and flow cytometry. Results: Left ventricular radius was increased in SHR-Failure compared to SHR-Non-Failure (p<0.01), and in SHR-ISO compared to SHR-Control (saline administration) (p<0.01), hence confirming the presence of cardiac dilatation in both models. Although, cardiac myocyte length vi was increased in all SHR groups compared to WKY (p<0.001), no differences were observed between SHR-Failure and SHR-Non-Failure, or between SHR-ISO and SHR-Control. No differences in cell length:width ratios or in cell widths were evident between the groups. The flow cytometry data confirmed the results obtained for cardiac myocyte lengths using microscopy. Moreover, a linear correlation (r=0.46, p=0.002) between flow cytometry and microscopy cardiac myocyte lengths was observed. Importantly, no relationships were evident between left ventricular radius and cardiac myocyte length (r=0.12, p=0.42 and r=0.14, p=0.35 for microscopic and flow cytometry lengths respectively). Conclusion: The results from the present study show that although pressure-overload hypertrophy is associated with lengthening of cardiac myocytes, no further changes occur with cardiac dilatation. Hence, alterations in cardiac myocyte dimensions do not contribute to the development of cardiac dilatation in pressure-overload models.
M.Sc.(Med.), Faculty of Health Sciences, University of the Witwatersrand, 2010
Keywords: Heart Hypertrophy; Myocardium